Reactivity of bis[{2, 6-(dimethylamino)methyl}phenyl]telluride with Pd(ii) and Hg(ii): isolation of the first Pd(ii) complex of an organotellurenium cation as a ligand. (6th August 2019) - Gupta, Anand K.; Deka, Rajesh; Singh, Harkesh B.; Butcher, Ray J.
Abstract : The first complex of an organotellurenium cation as a ligand with Pd(ii ) is reported. Abstract : Intramolecularly coordinated homoleptic diorganotelluride L2 Te (6 ) [where L = 2, 6-(Me2 NCH2 )2 C6 H3 ] was synthesized and its reactions with Pd(ii ) and Hg(ii ) precursors were explored. The reaction of6 with SO2 Cl2 and K2 PdCl4 resulted in the formation of the first example of a Pd(ii ) complex, LTePdCl3 (7 ), with any organotellurenium cation (LTe + ) as a ligand. When diorganotelluride6 was reacted with HgCl2, the reaction afforded the tellurenium cation [LTe]2 + [Hg2 Cl4 ] 2− (8 ). The reaction of6 with [(PhCN)2 PdCl2 ] afforded the Pd(ii )–telluroether complex L2 TePdCl2 (9 ). Diorganotelluride6 and complexes (7–9 ) were characterized by single-crystal X-ray diffraction studies. The crystallographic studies suggested that in complex7, the Te(ii ) center was 'ambiphilic' in nature in the sense that while Te(ii ) acted as a donor to the Pd(ii ) ion, at the same time, it accepted electrons from the N-donor side arms via secondary bonding interactions. The donation of electrons from Te(ii ) to Pd(ii ) in complex7 was further substantiated by Natural Bond Order (NBO) analysis.